Evolution of cartographic aggression by India: A study of Limpiadhura to Lipulek - Bhusal, Jagat K (Geographical Journal of Nepal, 2020)
Nepal is a sovereign country since its history and has never been colonized. In course of time, once a greater Nepal shrunk to present territory after its defeat in the Anglo-Nepal War (1814–15) and since the signing of the border treaty (Between the East India Company and the Raja of Nepal) which is known as the Sugauli Treaty of 1816. The defeat fixed the river Kali as the border in the west and the Mechi in the east on the hilly regions whereas there are border pillars (Jange Pillars) on the southern plains. The territorial issue between Nepal and India on the north-west border, especially up to the source of the Kali river is reviewed in this paper. Interpretations of the relevant documents and correspondences, reviewed papers, articles in periodicals and newspapers, and historical maps are critically made with reference to the recent freely available google maps and political maps published by Nepal and India. British-India after the Sugauli treaty and also India after the independence realized the importance of the Gunji-Kuti area, Lipulek pass and Kalapani and made the unilateral cartographic manipulation on the North-west border of Nepal. It is found that the borderline swinging over the century clearly indicated that the encroachment of about 400 sq. km land of Nepal contravened the spirit of the Sugauli Treaty.